Introduction to NBER Symposium on the October 1987 Crash - Grossman, Sanford J. (Review of Financial Studies, 1990)
The stock market crash of October 1987 led to a boom in conferences, commissions, and studies of the stock market. In almost each case, the participants would try to understand the events of October 1987 by a detailed analysis or description of events during the particular days of high volatility. Of course, to us economists there was nothing qualitatively unusual about October 19, 1987; the stock market moved, and we have no model that succeeds in explaining the magnitude or sources of daily stock market volatility for that day or any other day. When asked by the National Bureau of Economic Research to organize yet another conference on this subject, I decided that it was time to put these events in a historical perspective and try to understand them in the context of longer time periods and broader models. The papers collected in this symposium issue admirably succeed in broadening...